2016
DOI: 10.1111/1348-0421.12405
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression, peripheral inflammation and invasive infection from endogenous gut microbiota activate retinal microglia in mouse models

Abstract: Although its actual role in the progression of degenerative processes is not fully known, the persistent activated state of retinal microglia and the concurrent secretion of inflammatory mediators may contribute to neuronal death and permanent vision loss.Our objective was to determine whether non-ocular conditions (immunosuppression and peripheral inflammation) could lead to activation of retinal microglia. Mouse models of immunosuppression induced by cyclophosphamide and/or peripheral inflammation by chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…The LPS-induced microglial activation observed in P23H rat retinas is in agreement with our previous works and those by others, showing that systemic infections caused by cytomegalovirus 15 or Candida albicans 16 , as well as peripheral insults 17 are capable of triggering microglial activation and increasing the quantity of microglial cells in the retina. The higher number of Iba1-positive cells in the retina of LPS-injected P23H rats could be caused by migration of inflammatory macrophages, myeloid precursors, or inflammatory monocytes, or by the proliferation of retinal microglia, as these cell types are able to proliferate in situ once they have differentiated 36 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The LPS-induced microglial activation observed in P23H rat retinas is in agreement with our previous works and those by others, showing that systemic infections caused by cytomegalovirus 15 or Candida albicans 16 , as well as peripheral insults 17 are capable of triggering microglial activation and increasing the quantity of microglial cells in the retina. The higher number of Iba1-positive cells in the retina of LPS-injected P23H rats could be caused by migration of inflammatory macrophages, myeloid precursors, or inflammatory monocytes, or by the proliferation of retinal microglia, as these cell types are able to proliferate in situ once they have differentiated 36 .…”
Section: Discussionsupporting
confidence: 93%
“…Also, retinal neurodegenerative diseases, such as retinitis pigmentosa (RP) 3 , age-related macular degeneration 12 , and glaucoma 13 , 14 are concomitant with chronic microglial activation and neuroinflammatory process. Retinal microglial cells may also be activated by systemic infection by fungus or virus 15 , 16 and by immunosuppression or peripheral inflammation 17 , which could worsen the degenerative process. However, the mechanisms by which systemic inflammation and microglial activation exert their effects on chronic neurodegeneration are not yet widely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Different neurotransmitters are also known to activate microglia via their respective receptors, such as purinergic receptors, glutamate receptors, dopaminergic receptors and cholinergic receptors [9]. The immune cells and molecules (e.g., complement, inflammasome associated protein, gut microbiota, and the bacterial secreted metabolisms [19,20,21]) known to induce peripheral inflammation can also induce microglial activation.…”
Section: Microglia Are the Central Modulators Of Neuroinflammationmentioning
confidence: 99%
“…In this context, a few recent studies have linked gut microbiome changes with some retinal degenerative diseases [33,34], including age-related macular degeneration (AMD) [35][36][37][38][39], glaucoma [40][41][42][43] and diabetic retinopathy [44], even though the published results vary depending on the type and stage of the disease and between studies. On the other hand, in a previous study we have demonstrated that invasive infection from gastrointestinal microbiome can induce activation of retinal microglia [45], the primary resident immune cell of the retina.…”
mentioning
confidence: 84%